2008
DOI: 10.1021/ma8009454
|View full text |Cite
|
Sign up to set email alerts
|

Microphase Separation and Shear Alignment of Gradient Copolymers: Melt Rheology and Small-Angle X-Ray Scattering Analysis

Abstract: The degree of microphase or nanophase segregation in gradient copolymers with compositions varying across the whole copolymer backbone is studied via low-amplitude oscillatory shear (LAOS) measurements and small-angle X-ray scattering (SAXS). Studies are done as a function of comonomer segregation strength, molecular weight (MW), gradient architecture and temperature. Controlled radical polymerization is used to synthesize strongly segregating styrene/4-acetoxystyrene (S/AS) and the more weakly segregating S/n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 88 publications
3
87
0
Order By: Relevance
“…The role of macromolecular architecture-i.e., block sequences like triblocks, multiblocks, and gradient copolymers or branching like star and graft block copolymers-has been explored in length with respect to the different aspects of the rheological response discussed above (mainly linear viscoelasticity, ODT, and OOT). The key findings are qualitatively similar to those reported above [92][93][94]. The observed quantitative differences are attributed to the architecture and often rationalized theoretically [90,95,96].…”
Section: Other Topologiessupporting
confidence: 86%
See 1 more Smart Citation
“…The role of macromolecular architecture-i.e., block sequences like triblocks, multiblocks, and gradient copolymers or branching like star and graft block copolymers-has been explored in length with respect to the different aspects of the rheological response discussed above (mainly linear viscoelasticity, ODT, and OOT). The key findings are qualitatively similar to those reported above [92][93][94]. The observed quantitative differences are attributed to the architecture and often rationalized theoretically [90,95,96].…”
Section: Other Topologiessupporting
confidence: 86%
“…Moreover they do not have to be pure homopolymers. Many block copolymers used in applications are gradient or tapered block copolymers whose composition varies gradually along the chain or the blocks from A-rich at one end to B-rich at the other end [12][13][14][15][16][17]. It is nearly impossible to list the huge variety of block copolymers that have been synthesized and investigated.…”
Section: Architecture and Compositionmentioning
confidence: 99%
“…60 Reports in the literature have shown that the control of the gradient strength was an elegant way of driving the self-assembly of such amphiphilic copolymers. 61−63 ■ ASSOCIATED CONTENT…”
Section: Discussionmentioning
confidence: 99%
“…(For a review and comparison of gradient copolymer structure relative to that of other copolymers, see ref. 49.) Using self-consistent field theory, Shull 41 predicted that gradient copolymers exhibit a substantially lower CMC than do block copolymers of similar MW and composition.…”
Section: Introductionmentioning
confidence: 99%